2009
DOI: 10.1016/j.neurobiolaging.2007.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Differential age effects on cerebral blood flow and BOLD response to encoding: Associations with cognition and stroke risk

Abstract: Changes in the cerebrovascular system due to age or disease can significantly alter the bloodoxygenation-level-dependent (BOLD) signal and complicate its interpretation. The simultaneous acquisition of arterial spin labeling (ASL) and BOLD data represents a useful technique to more fully characterize the neurovascular underpinnings of functional brain response to cognition. We conducted a functional magnetic resonance imaging (FMRI) study of episodic memory encoding to investigate whether age is related to cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 79 publications
7
76
1
1
Order By: Relevance
“…In a similar vein, these results provide evidence against the notion that the observed reduction in BOLD activation in older adults during the resting state is due to age-related differences in cerebral vasculature alone (Bangen et al, 2009;D'Esposito, Deouell & Gazzaley, 2003;Kannurpatti et al, 2010 (Balsters et al, 2013).…”
Section: Discussionsupporting
confidence: 50%
“…In a similar vein, these results provide evidence against the notion that the observed reduction in BOLD activation in older adults during the resting state is due to age-related differences in cerebral vasculature alone (Bangen et al, 2009;D'Esposito, Deouell & Gazzaley, 2003;Kannurpatti et al, 2010 (Balsters et al, 2013).…”
Section: Discussionsupporting
confidence: 50%
“…Similarly, this association has been detected in normally aging older adults who later converted to MCI (de Leon et al 2001). Bangen et al (2007) have also shown robust associations between resting cerebral blood flow in the medial temporal lobe and CVD risk in cognitively intact healthy older adults. Silvestrini et al (2006) have also demonstrated that altered cerebrovascular hemodynamics (i.e., elevated cerebral vasomotor reactivity to hypercapnia) was associated with hastened cognitive decline in AD patients over 1 year.…”
Section: Vascular Contributions To Alzheimer's Disease and Its Prodromementioning
confidence: 85%
“…Previous results from clinical imaging and molecular studies have suggested a link between CVRF, structural deformities of brain microvessels (including arterial stiffness and microvascular damage), and the risk of dementia (Bell et al 2009;Grammas 2011a). Chronic cerebral blood flow deficits secondary to conditions such as diabetes, hypertension, and atherosclerosis, as well as heart failure-related microembolism, may all lead to decreased oxygen and glucose supply to the brain, as well as local toxic or metabolic disturbances (KumarSingh 2008;Bangen et al 2009;Menon and Kelley 2009). It has been suggested that microvascular changes secondary to chronic cerebral blood flow reductions might trigger the characteristic neuropathological changes of AD, such as aggregates of amyloid β-peptide (de la Torre 1999; de la Torre et al 2003).…”
Section: Discussionmentioning
confidence: 99%